Ionic liquid induced changes in the properties of aqueous zwitterionic surfactant solution - Behera, Kamalakanta (Langmuir : the ACS journal of surfaces and colloids, 2008)
Modifying properties of aqueous surfactant solutions by addition of external additives is an important area of research. Unusual properties of ionic liquids (ILs) make them ideal candidates for this purpose. Changes in important physicochemical properties of aqueous zwitterionic N-dodecyl- N, N-dimethyl-3-ammonio-1-propanesulfonate (SB-12) surfactant solution upon addition of hydrophilic IL 1-butyl-3-methylimidazolium tetrafluoroborate, [bmim][BF 4], are reported. Dynamic light scattering results indicate a dramatic reduction in the average micellar size in the presence of [bmim][BF 4]; micellar (or micelle-like) aggregation in the presence of as high as 30 wt % [bmim][BF 4] is confirmed. Responses from fluorescence probes are used to obtain critical micelle concentration (cmc), aggregation number ( N agg), and dipolarity and microfluidity of the micellar pseudophase of aqueous SB-12 in the presence of [bmim][BF 4]. In general, increasing the amount of [bmim][BF 4] to 30 wt % results in decrease in N agg and increase in cmc. Increase in the dipolarity and the microfluidity of the probe cybotactic region within the micellar pseudophase is observed on increasing [bmim][BF 4] concentration in the solution. It is attributed to increased water penetration into the micellar pseudophase as [bmim][BF 4] is added to aqueous SB-12. It is proposed that IL [bmim][BF 4] behaves similar to an electrolyte and/or a cosurfactant when present at low concentrations and as a polar cosolvent when present at high concentrations. Electrostatic attraction between cation of IL and anion of zwitterion, and anion of IL and cation of zwitterion at low concentrations of [bmim][BF 4] is evoked to explain the observed changes. Presence of IL as cosolvent appears to reduce the efficiency of micellization process by reducing the hydrophobic effect